All‐Manganese‐Based Binder‐Free Stretchable Lithium‐Ion Batteries. Issue 18 (23rd May 2017) - Gu, Taoli; Cao, Zeyuan; Wei, Bingqing
Abstract : Advanced electrode materials with bendability and stretchability are critical for the rapid development of fully flexible/stretchable lithium‐ion batteries. However, the sufficiently stretchable lithium‐ion battery is still underdeveloped that is one of the biggest challenges preventing from realizing fully deformable power sources. Here, a low‐temperature hydrothermal synthesis of a cathode material for stretchable lithium‐ion battery is reported by the in situ growth of LiMn2 O4 (LMO) nanocrystals inside 3D carbon nanotube (CNT) film networks. The LMO/CNT film composite has demonstrated the chemical bonding between the LMO active materials and CNT scaffolds, which is the most important characteristic of the stretchable electrodes. When coupled with a wrinkled MnO x /CNT film anode, a binder‐free, all‐manganese‐based stretchable full battery cell is assembled which delivers a high average specific capacity of ≈97 mA h g −1 and stabilizes after over 300 cycles with an enormous strain of 100%. Furthermore, combining with other merits such as low cost, natural abundance, and environmentally friendly, the all‐manganese design is expected to accelerate the practical applications of stretchable lithium‐ion batteries for fully flexible and biomedical electronics. Abstract : An all‐manganese‐based binder‐free stretchable lithium‐ion battery with 100% stretchability is prepared based on the LiMn2 O4 /carbon nanotube (CNT) cathode and MnO x /CNT anode. A little capacity decay of 0.04% per cycle in the battery under the repeated unstretched and stretched states is achieved.